2019
DOI: 10.1093/glycob/cwy112
|View full text |Cite
|
Sign up to set email alerts
|

Total loss of GM3 synthase activity by a normally processed enzyme in a novel variant and in all ST3GAL5 variants reported to cause a distinct congenital disorder of glycosylation

Abstract: ST3GAL5-CDG is a rare syndrome which is caused by variant GM3 synthases, the enzyme involved in the biosynthesis of a-b-c-series gangliosides. Here we report a novel homozygous ST3GAL5 variant, p.Gly342Ser, in a patient suffering from failure to thrive, severe hearing, visual, motor, and cognitive impairment, and respiratory chain dysfunction. A GM3 synthase assay towards the natural acceptor substrate lactosylceramide was performed upon transfection in HEK-293T cells of expression plasmids carrying wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Altogether, this data is in agreement with the current hypothesis that the total absence of gangliosides is responsible for the general lack of neuron homeostasis, leading to inflammation and, consequently, loss of several functions [105]. However, many patients present mildly elevated blood lactate and their cells have an impaired respiratory chain function [25,100]. In this context, the hypothesis that impaired autophagy and, in particular, mitophagy may be involved in the disease pathogenesis should be kept in mind.…”
Section: Specific Diseases Of Ganglioside Biosynthesis Determiningsupporting
confidence: 88%
See 2 more Smart Citations
“…Altogether, this data is in agreement with the current hypothesis that the total absence of gangliosides is responsible for the general lack of neuron homeostasis, leading to inflammation and, consequently, loss of several functions [105]. However, many patients present mildly elevated blood lactate and their cells have an impaired respiratory chain function [25,100]. In this context, the hypothesis that impaired autophagy and, in particular, mitophagy may be involved in the disease pathogenesis should be kept in mind.…”
Section: Specific Diseases Of Ganglioside Biosynthesis Determiningsupporting
confidence: 88%
“…Some of these patients lack clinical seizures or were initially able to crawl, as originally reported only for two siblings carrying the compound C195S/G201A mutations [103]. Accordingly, we have recently shown that all reported mutations abolish any detectable enzyme activity, without differences between the single mutations [100]. Moreover, we also found a normal localization of the variant ST3GAL5s.…”
Section: Specific Diseases Of Ganglioside Biosynthesis Determiningsupporting
confidence: 76%
See 1 more Smart Citation
“…The ganglioside patterns in mice mimic those in a human newborn with SD and TSD, and mouse models have greatly advanced our knowledge of ganglioside metabolism and therapy of LSDs [14]. However, in certain types of LSDs, the symptoms developing in mice were less severe than those in humans suggesting a greater complexity of the human syndrome [15]. For example, the SD and TSD disease models in mice do not completely recapitulate the human phenotype.…”
Section: Gangliosidesmentioning
confidence: 99%
“…The variant associated with Salt & Pepper Syndrome, ST3GAL5 c.1063G>A (p.Glu355Lys), encodes for a mutant form of the enzyme lacking any enzymatic activity [9]. A more prevalent variant identified in the Amish population, c.862C>T (p.Arg288Ter), encodes for a truncated and inactive enzyme [9,10].…”
Section: Introductionmentioning
confidence: 99%